2007
DOI: 10.2807/esw.12.11.03158-en
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Salmonella Typhimurium infection traced to imported cured sausage using MLVA-subtyping

Abstract: On 28 November 2006, a patient in Norway was diagnosed with Salmonella Typhimurium infection. He contacted the district food safety office in Trondheim as he suspected the source to be Spanish-produced cured sausages he had bought on a ferry between Kiel, Germany and Oslo, Norway in October 2006.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Clustering confirmed by both subtyping methods provides strong evidence for true genetic relatedness, while discordant results can be difficult to interpret. Similar to our study which suggested diversification of both PFGE and MLVA patterns on individual farms, the diversification of PFGE and MLVA patterns has been reported during human salmonellosis outbreaks, even though diversification rates are difficult to estimate (23,50,64,67). In such instances, the use of additional information, e.g., epidemiologic data, antimicrobial resistance patterns, or prior knowledge of subtype diversity, can be very useful for inferring relationships between isolates.…”
Section: Discussionsupporting
confidence: 82%
“…Clustering confirmed by both subtyping methods provides strong evidence for true genetic relatedness, while discordant results can be difficult to interpret. Similar to our study which suggested diversification of both PFGE and MLVA patterns on individual farms, the diversification of PFGE and MLVA patterns has been reported during human salmonellosis outbreaks, even though diversification rates are difficult to estimate (23,50,64,67). In such instances, the use of additional information, e.g., epidemiologic data, antimicrobial resistance patterns, or prior knowledge of subtype diversity, can be very useful for inferring relationships between isolates.…”
Section: Discussionsupporting
confidence: 82%
“…Outbreak investigations overseas have highlighted that S. Typhimurium MLVA loci appear stable over short periods of time although single-locus variants have been identified [28][29][30][31]. Outbreak investigations overseas have highlighted that S. Typhimurium MLVA loci appear stable over short periods of time although single-locus variants have been identified [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Strains are assigned a numerical code corresponding to the numbers of tandem repeats in the target loci, and this provides an unambiguous dataset that is easily exchanged between laboratories (Larsson et al 2013). As MLVA has been reported to be highly discriminatory as well as fast and fairly cheap to perform, the method it is now being used by many European laboratories for Salmonella Typhimurium cluster detection and outbreak investigations (Cho et al 2007;Nyg ard et al 2007;Torpdahl et al 2007).…”
Section: Introductionmentioning
confidence: 99%